Controlled Synthesis of Hollow PbS‐TiO2 Hybrid Structures through an Ion Adsorption–Heating Process and their Photocatalytic Activity. Issue 22 (13th October 2017) - Xia, Hongbo; Wu, Suli; Zhang, Shufen
Abstract: Hollow hybrid nanostructures have received significant attention because of their unique structural features. This study reports a facile ion adsorption–heating method to fabricate hollow PbS‐TiO2 hybrid particles. In this method, the TiO2 spheres used as a substrate material to grow PbS are aggregates of many small amorphous TiO2 particles, and each small particle is covered with thioglycolic acid ligands through Ti 4+ –carboxyl coordination. When Pb 2+ ions are added to a colloidal solution of these TiO2 spheres, these ions are adsorbed by sulfhydryl (‐SH) groups to form metal thiolates, and the C−S bond is dissociated by heating to release S 2− . The S 2− ions react with Pb 2+ ions to form PbS without additive sulfur sources. Additionally, the amorphous TiO2 spheres are transformed into the anatase phase during the heating process. As a result, the crystallization of TiO2 spheres along with the formation of PbS is simultaneously carried out by heating. During the heating process, owing to the Kirkendall effect of S 2− diffusion and the Ostwald ripening effect of the crystallization of amorphous TiO2 spheres, PbS‐TiO2 hollow hybrid structures can be obtained. The XRD and XPS characterizations proved the formation of anatase TiO2 and PbS. The TEM characterization confirmed the formation of hollow structures in the PbS‐TiO2 hybrid sample. The photocatalytic activity of the hollow PbS‐TiO2 hybrid spheres have been investigated for the degradation of Cr 6+ under visible light. The results show that hollow PbS‐TiO2 hybrid spheres exhibited the highest photocatalytic activity, in which almost all the Cr 6+ was degraded after 140 min. Abstract : All hollowed : Hollow PbS‐TiO2 hybrid structures were obtained by a facile ion absorption–heating process. Pb 2+ ions interacted with the ‐SH groups of thioglycolic acid ligands on the surfaces of the aggregated TiO2 spheres, then dissociation of the C−S bonds by heating resulted in formation of PbS. As a result, hollow PbS‐TiO2 hybrid structures were formed due to the Kirkendall effect of S 2− diffusion and Ostwald ripening effect of the crystallization of amorphous TiO2 spheres during the reaction (see figure).